Heat transfer to newtonian and non-newtonian fluids in cross-corrugated chevron-type plate heat exchangers: numerical approach. - Fernandes, Carla S. (2011)
Food fluids are frequently processed in plate heat exchangers (PHEs) and usually behave as non-Newtonian fluids, this behavior being scarcely considered for PHEs design purposes (Rene et al., 1991). Moreover, many food fluids processed in PHEs have a high viscosity and therefore, data obained in laminar flow regime is useful to practical applications (Rene et al., 1991); Metwally and Manglik, 2002, Fernandes et al., 2005, 2006, 2007).